Morita therapy for depression in adults: A systematic review and meta-analysis. (November 2018) - Jia, Yong; Li, Min; Cheng, Zhaohua; Cui, Lianzhi; Zhao, Jinping; Liu, Yufei; Leng, Minmin; Li, Feng; Chen, Li
Highlights: Morita therapy significantly reduced the severity of depression symptoms as an adjunctive therapy. Remission rate in the Morita therapy plus pharmacotherapy group was better than in the pharmacotherapy alone group. Higher-quality, multicultural and larger sample trials are required for further research to support the clinical application of Morita therapy. Abstract: Morita therapy is a systematic psychological therapy that aims to improve everyday functioning rather than target specific symptoms. However, there has been no systematic review evaluating the evidence of the effectiveness of Morita therapy in the treatment of depression. The aim of this study was to assess the clinical efficacy of Morita therapy in combination with pharmacotherapy in patients 18 and older who were diagnosed with current depressive disorder. A total of 840 patients with depression from 11 randomized controlled trial (RCT) studies were included in this meta-analysis after a literature search of 10 databases was performed from database inception to July 1, 2017. All the eligible studies were determined to have an unclear or high risk of bias. Morita therapy plus pharmacotherapy was significantly superior to pharmacotherapy alone in reducing depression severity. The remission rate of the Morita therapy plus pharmacotherapy group was better than that of the pharmacotherapy alone group. Morita therapy significantly reduced depression severity symptoms and improved the remission rate. Due to the relatively weak quality of the included studies, definitive conclusions cannot be made. Thus, multi-center, well-designed clinical trials with larger cohorts are urgently needed to support the clinical application of Morita therapy.